1999
DOI: 10.1093/nar/27.8.1847
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of overlapping genes in the genomes of Mycoplasma genitalium and Mycoplasma pneumoniae

Abstract: Overlapping genes are defined, in this paper, as a pair of adjacent genes whose coding regions are partly overlapping. We systematically analyzed all overlapping genes in the genomes of two closely related species: Mycoplasma genitalium and Mycoplasma pneumoniae. Careful comparisons were made for homologous genes that are overlapped in one species but not in the other. This comparative analysis allows us to propose a model of how overlapping genes emerged in the course of evolution. It was found that overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 11 publications
4
45
0
Order By: Relevance
“…strain SJY1 (23,24). In S33, ndhA and ndhB overlap 4 bp, which is common for the genes of multiple subunits enzyme in microorganisms and is helpful for rapid cotranscription and translation and their regulation (62,63). Interestingly, there is a 26-kb distance between ndhAB-hno and pno-hsh, where 6 of 12 ORFs encode mobile element proteins, suggesting that these genes might come from other bacteria by the way of lateral gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…strain SJY1 (23,24). In S33, ndhA and ndhB overlap 4 bp, which is common for the genes of multiple subunits enzyme in microorganisms and is helpful for rapid cotranscription and translation and their regulation (62,63). Interestingly, there is a 26-kb distance between ndhAB-hno and pno-hsh, where 6 of 12 ORFs encode mobile element proteins, suggesting that these genes might come from other bacteria by the way of lateral gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…This has all the characteristics of an Internal Overlap: the Overlapping protein is thought to be younger than the much longer replicase (Keese and Gibbs 1992)-which we can confirm with our PDI measures for the two genes-and the overlap has arisen via a +1 frameshift. In bacteria, a comparative analyses of the genomes of Mycoplasma genitalium and Mycoplasma pneumoniae found some relatively long Terminal Overlaps, which appeared to be incidental elongations of the coding region by loss of the 3Ј stop codon (Fukuda et al 1999). The investigators found poor conservation of these elongated regions compared with homologs in other taxa, and suggested that these regions had little or no functional role at present; they appear to us to be other examples of gene overlap in the process of acquiring function.…”
Section: Discussionmentioning
confidence: 99%
“…Second, unlike genomic sequencing, where both strands are sequenced, RNA-Seq experiments are usually strand-specific. To be effective, transcriptome assemblers will need to take advantage of strand information to resolve overlapping sense and anti-sense transcripts [11][12][13][14] . Finally, it is generally difficult for short read assemblers to resolve repeat structures in a genome assembly; this problem is exacerbated during transcriptome assembly because transcript variants from the same gene can share many exons..…”
mentioning
confidence: 99%